EVOLVE: The Australian Rheumatology Association's 'top five' list of investigations and interventions doctors and patients should question. Issue 2 (7th February 2018) - Morrisroe, Kathleen; Nakayama, Ayano; Soon, Jason; Arnold, Mark; Barnsley, Les; Barrett, Claire; Brooks, Peter M.; Hall, Stephen; Hanrahan, Patrick; Hissaria, Pravin; Jones, Graeme; Katikireddi, Veera S.; et al.
Abstract: Background: The EVOLVE (evaluating evidence, enhancing efficiencies) initiative aims to drive safer, higher‐quality patient care through identifying and reducing low‐value practices. Aims: To determine the Australian Rheumatology Association's (ARA) 'top five' list of low‐value practices. Methods: A working group comprising 19 rheumatologists and three trainees compiled a preliminary list. Items were retained if there was strong evidence of low value and there was high or increasing clinical use and/or increasing cost. All ARA members (356 rheumatologists and 72 trainees) were invited to indicate their 'top five' list from a list of 12‐items through SurveyMonkey in December 2015 (reminder February 2016). Results: A total of 179 rheumatologists (50.3%) and 19 trainees (26.4%) responded. The top five list (percentage of rheumatologists, including item in their top five list) was: Do not perform arthroscopy with lavage and/or debridement for symptomatic osteoarthritis of the knee nor partial meniscectomy for a degenerate meniscal tear (73.2%); Do not order anti‐nuclear antibody (ANA) testing without symptoms and/or signs suggestive of a systemic rheumatic disease (56.4%); Do not undertake imaging for low back pain for patients without indications of an underlying serious condition (50.8%); Do not use ultrasound guidance to perform injections into the subacromial space as it provides no additional benefit in comparison to landmark‐guided injection (50.3%) and Do not order anti‐double‐stranded DNA antibodies in ANA negative patients unless the clinical suspicion of systemic lupus erythematosus remains high (45.3%). Conclusions: This list is intended to increase awareness among rheumatologists, other clinicians and patients about commonly used low‐value practices that should be questioned.